Phenolic compounds in the kola nut (Cola nitida and Cola acuminata) (Sterculiaceae) in Africa - Odebode, A C (Revista de Biología Tropical, 1996)
Phenolic compounds and total phenol in the two edible Cola species, C. nitida and C. acuminata, were anaIyzed by paper chromatogtáphy, using fiye solyent systems. N-butyl alcohol, acetic acid, water in the proportion of (4:1:5) yielded the highest,number of phenolic compounds; catechin, quinic acid, tannic acid, and chlorogenic acid were deterrnined to be the' major components of the kola nut. There were marked differences in the arnount of total phenol in each species and ¡;olor characteristics-related differences within species. The percent total phenol in C. nitida was higher than in C. acuminata.